2010
DOI: 10.2174/187221310789895630
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Allergy in Healthcare Workers

Abstract: Occupational healthcare may expose to various allergens and irritants. Thus, the allergic manifestations in nursing staff are frequent and their prevalence is increasing all over the world. In fact, many new substances continuously appear in the medical practices. These allergic manifestations include a wide spectrum of clinical symptoms such as ocular, nasal and especially bronchial symptoms, which can be isolated or associated. These diseases can be a source of many problems related to the occupational aptit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This question was several times reconfirmed and this is a strength compared to the previously published report where occupational sensitization was assumed only based in occupational exposure (8). Technical prevention is based on risk elimination, possibly replacing products or substances responsible for allergic manifestations to non-sensitizing agents (2). Allergic risk prevention is essential, and must be rapidly implemented to prevent incapacitating occupational diseases.…”
Section: Case Reportmentioning
confidence: 91%
See 2 more Smart Citations
“…This question was several times reconfirmed and this is a strength compared to the previously published report where occupational sensitization was assumed only based in occupational exposure (8). Technical prevention is based on risk elimination, possibly replacing products or substances responsible for allergic manifestations to non-sensitizing agents (2). Allergic risk prevention is essential, and must be rapidly implemented to prevent incapacitating occupational diseases.…”
Section: Case Reportmentioning
confidence: 91%
“…It can occur by various routes, and contact with spilled drugs and powder or foam inhalation are the most common (4). Cutaneous sensitization is often fast, in weeks or months (2), and was probably enhanced in this patient by a damaged skin barrier leading to local and systemic immune responses (17). Clearly identified risk factors for drug-induced anaphylaxis, like female sex or concurrent medications, do not include professional exposure (1), although some studies point out that HCP seem to have an increased risk of penicillin allergy (18,19).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The main source of workplace exposure is use of powdered latex gloves by healthcare workers. In studies on hospital personnel, latex sensitivity was found to be 3-5 times higher among nurses and doctors than among personnel not involved in patient care [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The prevalence of latex allergy in healthcare settings is reported to be affected by several factors, including atopy [21][22][23], frequency of glove use, prior or current hand dermatitis and also the long exposure-times when working in hospitals [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the present study found that the likelihood of AR, asthma, and ARS among health care workers was much lower. One explanation is that tolerance to various allergens and irritants could occur in an occupational environment (46).…”
mentioning
confidence: 99%